Secularism and liberalism in contemporary Argentina: Neoliberal responses, initiatives, and criticisms of Pope Francis - Semán, Pablo (Social compass, 2018)
The role of Jorge Bergoglio as the head of the Catholic Church has provoked political positioning in Argentina, which reveals new forms of articulation between secularism and politics. While progressive sectors connected to the Kirchnerist government initially viewed Pope Francis and his theology of the people with mistrust, they currently see him as an ally in the defence of social initiatives. From the conservative perspective, the trajectory has been exactly the opposite. Although they initally saw the Pope as an ally to help undermine populism, they soon discovered serious obstacles in the way. As a response, they raised the banner of laïcité and called into question the close relationship between politics and the Catholic Church. In this context, we will analyse the reactions, initiatives, and critical arguments, which surfaced around this limited secularism in political life, the mass media, and public space. In other words, we will observe a displacement in which social conservatism is not necessarily of a Catholic fundamentalist variety, and neoliberalism launches its own secularising tradition.